Enhancement of Fracture Toughness of NiTi Alloy by Controlling Grain Size Gradient - Kai Huang; Zhongzheng Deng; Hao Yin (Nanomaterials)
Fracture toughness is a critical indicator for the application of NiTi alloys in medical fields. We propose to enhance the fracture toughness of NiTi alloys by controlling the spatial grain size (GS) gradient. Utilizing rolling processes and heat treatment technology, three categories of NiTi alloys with distinct spatial GS distributions were fabricated and subsequently examined through multi-field synchronous fracture tests. It is found that the one with a locally ultra-high GS gradient (20 nm−3.4 μm) has significantly enhanced fracture toughness, which is as high as 412% of that of the normally distributed nano-grains with an average GS of 8 nm and 178% of that of the coarse-grains with an average GS of 100 nm. Theoretical analysis reveals that in such a gradient structure, phase transition in the coarse-grained matrix greatly absorbs the surface energy of subcritical and stable propagation. Meanwhile, the locally non-uniform GS distribution leads to deviation and tortuosity of the crack path, increasing the critical fracture stress. Furthermore, the nanocrystalline clusters distributed in the form of network nodes reduce the stress intensity factor due to their higher elastic modulus compared to the coarse-grained matrix. This work provides guidance for developing new gradient nanostructured NiTi alloys with high fracture toughness.